Pengaruh Work Family Conflict, Modalpsikologis Dan Variabel Demografis Terhadap Kinerja Guru - Aisya Dewi Nashtya; Akhmad Baidun (‎‎‎TAZKIYA Journal of Psychology, 2017)
This study aims to examine the effect of work family conflict, psychological capital and demographic variables on the performance of 200 teachers. Sampling conducted using non probability sampling technique. Measurers used in this study consist of Individual Work Performance (IWP) to measure performance, then the authors make their own items to measure work family conflict and use Psychological Capital Questionnaire (PCQ-24) to measure psychological capital. Test the validity of measuring instruments using Confirmatory Factor Analysis (CFA) techniques and data analysis techniques using multiple regression analysis techniques. The results showed that there is a significant influence work family conflict, psychological capital and demographic variables on teacher performance of 26.6%. That is, the proportion of variance of performance explained jointly by work family conflict, psychological capital and demographic variable is 26.6% while the other 73.4% is influenced by other variables beyond this study. DOI :10.15408/tazkiya.v22i1.8165